Writing and Educational Experiences in Real Settings at a Colombian University - Narváez-Cardona, Elizabeth (Íkala, Revista de Lenguaje y Cultura, 2023)
In Latin America, there have been several institutional initiatives and research focused on writers' education in disciplinary and professional communities. However, there is a need for studies are needed that explore the relationships between writing and formative experiences in real environments, such as pre-practicums, placements, and internships. This article presents the emerging results of a qualitative research project that investigated undergraduate students' learnings in relation to the formative experiences they had in these environments. The analysis was done from the perspective of the students and other actors associated with pre-professional, professional, and placement practices, such as academic directors, coordinators, course instructors, and advisors. The study was carried out in four programs at a private Colombian university and was based on questionnaires and interviews with the above-mentioned actors. The analysis shows that the access, use, and production of discursive genres with socio-humanistic, academic, professional, or labor purposes are part of the learning associated with such formative experiences. Therefore, the results suggest that academic literacy advocates have a pedagogical opportunity to accompany practicums, internships, and placement practices, in order to enhance the reuse of knowledge, especially that related to writing.